Characteristic Times for the Fermi-Ulam Model - Hermes, Joelson D. Veloso [UNESP] (2021)
The mean Poincaré recurrence time as well as the Lyapunov time are measured for the Fermi-Ulam model. It is confirmed that the mean recurrence time is dependent on the size of the window chosen in the phase space where particles are allowed to return. The fractal dimension of the region is determined by the slope of the recurrence time against the size of the window and two numerical values are measured: (i) μ = 1 confirming normal diffusion for chaotic regions far from periodic domains and (ii) μ = 2 leading to anomalous diffusion measured inside islands of stability and invariant curves corresponding to regular orbits, a signature of local trapping of an ensemble of particles. The Lyapunov time is the inverse of the Lyapunov exponent. Therefore, the Lyapunov time is measured over different domains in the phase space through a direct determination of the Lyapunov exponent.